ما مدى تأثير جائحة كورونا (كوفيد - 19 -) على مستقبل المرجعية المحاسبية الدولية-رؤية تحليلية من منظور محاسبي-.: What Is The Impact Of The Corona Pandemic (Covid-19-) On The Future Of The International Accounting Reference - An Analytical Vision From An Accounting Perspective-. - عنون فؤاد,; ضويفي حمزة, (Journal of North African Economies, 2025)
This study addressed a major problem centered on the degree of impact of the Corona pandemic (Covid-19-) on current accounting practices on the one hand, and the future of accounting reference on the other, by specifying the requirements for preparing and presenting the financial statement in line with the developments of the current environment in light of the developments in standards (IAS/IFRS). The study reached the most important results: the spread of the Corona virus pandemic (Covid- 19-) led to the inability to apply some provisions of international accounting standards in order to prepare and present financial statements, which requires the necessity of continuity of work on developing the international accounting reference represented in (IAS/ IFRS) and make it more responsive to the requirements of the modern business environment.